Contributions of Enim Watershed in Production of Irrigation Rice Using Benefit and Cost Analysis - Yuli Andriani; T.Yuri M. Zagloel; R.H. Koestoer; M. Suparmoko (INSIST, 2017)
Abstract— Population growth impacts on accumulating basic need. Basic foodstuff of Indonesia people is rice. The rice is derived from paddy field. The availability of paddy land use need to be maintained due to the continuously of supporting aspects ie water, paddy field. Therefore,  it is necessary to manage rice crops to yield more production. Irrigation is one way to increase rice production. Irrigation plays an important role in the success of rice production. An important role of this irrigation should be assessed economically. The economic value of irrigation for paddy production needs to be studied. An important role of the irrigation should be assessed econmically. The economic value of irrigation for paddy production needs to be studied. Study of economic value is important so that people know that the irrigation water is an important contribution in the production of rice in addition to seeds, fertilizer and labor. It is necessary for economic calculation.This study aimed to quantify the economic value of watersheds to irrigate rice fields. Economic value calculation is conducted using benefit and cost benefit analysis on use of irrigation watershed in Cahaya Alam village. Muara Enim regency in South Sumatera of provinceKeywords— Enim watershed, irrigation, benefits and costs analysis